Using FTT-CAN to Combine Redundancy with Increased Bandwidth - Silva, Valter
Controller Area Network is yet widely used as the embedded network in safety critical applications, e.g. in the automotive domain. However, requirements have changed and dependability and bandwidth limitations led to the emergence of alternative networks such as FlexRay. Nevertheless there is still room to improve CAN to try to fulfill current requirements. In this paper it is proposed the use of FTT-CAN to achieve compromises between available bandwidth and fault tolerance in CAN based systems with multiple buses. The architecture and flexibility of FTT based systems enables a tight yet flexible control of redundancy and bandwidth usage without increasing the complexity of the nodes. The paper discusses different scenarios of operation of FTT-based multiple bus systems, analyzing the advantages and drawbacks of the envisaged solutions.